Synthesis, Crystal Structure and Magnetic Properties of a Novel Tetranuclear Oxo-Bridged Iron(Iii) Butterfly - Canon-Mancisidor, W; Canon-Mancisidor, W (2014)
A novel carboxylate/picolinate oxo-bridged iron(III) cluster, namely [Na2(H2O)8][Fe4(?-O) 2(O2CPh)7(pic)2]2· 2H2O (1) where pic = picolinate, has been obtained by reacting "basic iron benzoate" [Fe3O(O2CPh) 6(H2O)3](O2CPh) with sodium picolinate in acetonitrile. The compound has been characterized by elemental analysis and IR spectroscopy and its crystal structure has been determined by single-crystal X-ray diffraction. Variable-temperature magnetic susceptibility measurements in polycrystalline samples reveal moderate antiferromagnetic couplings leading to an S = 0 ground state. Theoretically computed values of the exchange constants in the title compound were also obtained with DFT calculations and were in agreement with the overall conclusions of the analysis of the experimental data. © 2013 Elsevier B.V. All rights reserved.